Wind power deployment in Germany: trade-offs of spatial planning instruments - Charlotte Geiger; Philip Tafarte; Elisabeth Wolfram; Paul Lehmann (Journal of Land Use Science)
Wind turbines may cause negative environmental impacts, such as residential disamenities or adverse effects for ecologically protected areas. Spatial planning policies are a common instrument to address these impacts, e.g. by excluding areas from wind power. While the targeted environmental impacts may be effectively reduced, spatial planning policies can cause trade-offs with untargeted environmental impacts. We assess these trade-offs in a spatial optimization model based on high-resolution GIS data of the potential areas for onshore wind power in Germany. We find that considerable trade-offs exist between environmental impacts, but not for the average levelized cost of electricity (LCOE) of wind power production. Combinations of spatial planning policies result in higher trade-offs. Additionally, we identify five underlying drivers for the size of trade-offs.